The dinosaur detectives in the Amazon rainforest - Baudet, Stephanie (Leicester : Sweet Cherry Publishing, 2016)
The Dinosaur Detectives is a fun filled adventure series following the story of Matt Sharp and his family as they hunt for dinosaur eggs. This fact meets fiction series is great for the young explorer.
Keywords: Dinosaurs -- Juvenile fiction; Action and adventure fiction